Fourth Canadian Conference on Computer and Robot Vision (CRV '07) 2007
DOI: 10.1109/crv.2007.20
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Face Image Logs that are Both Complete and Concise

Abstract: This paper describes a construct that we call a face image log. Face image logs are collections of time stamped images representing faces detected in surveillance videos. The techniques demonstrated in this paper strive to construct face image logs that are complete and concise in the sense that the logs contain only the best images available for each individual observed. We begin by describing how to assess and compare the quality of face images. We then illustrate a robust method for selecting high quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…This definition is consistent with most work on biometric quality, and a number of recent papers [8], [16], [5], [18], [17], [7], [4], [10] have looked at general image properties, such as contrast, sharpness, and illumination intensity. Luo [8] presents an instance of a general framework where quality is measured using Radial Basis Function (RBF) without relying on reference images for assessing quality.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…This definition is consistent with most work on biometric quality, and a number of recent papers [8], [16], [5], [18], [17], [7], [4], [10] have looked at general image properties, such as contrast, sharpness, and illumination intensity. Luo [8] presents an instance of a general framework where quality is measured using Radial Basis Function (RBF) without relying on reference images for assessing quality.…”
Section: Introductionsupporting
confidence: 59%
“…Hsu et al [7] showed the consistency and discrepancy between human quality ratings and machine quality scores using a classification-based score normalization process for various quality metrics. Fourney et al [4] define an image's quality based on its potential to lead to a correct identification when used with existing face recognition software. Nasrollahi et al [10] measure quality of faces in video sequences by combining features like outof-plane rotation, sharpness, brightness and resolution.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, the work published by Laganiere et al [6] is the only one that explicitly addresses the face logging problem building increasing quality image se quences. In that paper, the face quality estimation is given by the linear combination of three different measures: pose esti mation, illumination compensation and sharpness estimation, the last one being studied in the frequency domain.…”
Section: Related Workmentioning
confidence: 98%
“…There are many researches about optimal face acquisition in a surveillance camera or a single sequence of images [1][2][3][4]. Fourney et al [1] proposed a high quality face image selecting method by integrating 6 quality criteria with linear weighting.…”
Section: Introductionmentioning
confidence: 99%